Pengaruh Manajemen Kesiswaan, dan Manajemen Sarana Prasarana, Prestasi Belajar Siswa di Madrasah Tsanawiyah Raudhatul Mujawwiddin Kabupaten Tebo - Umi Tohiroh; Muhammad Anas Maarif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the influence of student management and facilities and infrastructure management on student learning achievement at MTs Raudhatul Mujawwidin, Tebo Regency. The research examines three aspects: the partial effect of student management on learning achievement, the partial effect of facilities and infrastructure management on learning achievement, and the simultaneous influence of both variables on student achievement. This study uses a quantitative approach with data analysis through statistical testing. The results indicate that student management has a significant partial effect on student learning achievement, as shown by a significance value of 0.013 (<0.05) and a t-count value of 2.509, which exceeds the t-table value of 1.654. Meanwhile, facilities and infrastructure management does not have a significant partial effect on learning achievement, with a significance value of 0.881 (>0.05) and a t-count value of 0.150. Simultaneously, student management and facilities and infrastructure management have a significant effect on student learning achievement, indicated by a significance value of 0.042 (<0.05). These findings show that effective student management plays an important role in improving academic achievement, while the availability and management of facilities and infrastructure require further optimization to provide a stronger contribution to learning outcomes.